Development of affective authentic assessment instruments for automotive engineering expertise in vocational school - Sudirman Rizki Ariyanto; Munoto Munoto; Muhaji Muhaji (Universitas Sarjanawiyata Tamansiswa, 2019)
Many factors influence Students’ low abilities in the affective domain, especially at the level of vocational schools (VHS). The lack of ability of teachers to develop affective authentic assessment instruments be one of the factors that influence it. Besides, designing authentic assessment instruments is not as easy affective cognitive assessment. This research uses ADDIE development model as a reference in developing affective authentic assessment instruments. There are five stages of ADDIE models, include analysis; (2) design; (3) development; (4) implementations; and (5) evaluation. Based on data analysis is known that instruments developed are valid, reliable, and practical to use in the learning process. This is evidenced from (1) the results of the validation by 4, 50 with a valid category; (2) the reliability test results amounted to 0.985 with a special category; and (3) test results practicality of 3.06 with a practical category.